Programs to Address Violence for Military Families: a Systematic Review - Dodge, Jessica (Journal of family violence, 2025)
PurposeFamily violence, encompassing intimate partner violence (IPV) and child maltreatment (CM), is a considerable public health issue affecting a large subset of the U.S. population. Military families may be exposed to unique risk factors for experiencing family violence. Interventions to address family violence that are specific to military and Veteran populations are critical to the military family wellbeing as they address the unique military context as well as military stressors. Though a number of these programs exist, to our knowledge, there has been no systematic effort to describe and evaluate these interventions. To address this issue, the present study employs systematic review methods to explore the following research questions: (1) What military family violence interventions are reported in the peer-reviewed literature? (2) What are the characteristics of these interventions? (3) How effective are these interventions?MethodsThis study utilized a systematic review following the PROSPERO (the International Prospective Register of Systematic Reviews) protocol, registration code CRD42022296207.ResultsThe initial search returned 3,666 sources. From these, 15 sources evaluating thirteen military family violence interventions were identified. About half of the studies evaluated interventions for Veterans and/or their partners (n = 7), one study was for both Veterans and Active Duty service members and/or their partners, four were solely for Active Duty service members and/or their partners and families, two studies were for Veterans alone, and one study addressed a system-level intervention. Only three studies examined child-level outcomes. All studies reported positive intervention outcomes covering a variety of treatment modalities (i.e., group, couples, individual, online, in-person), which ranged from improved anger management skills, including reduced yelling, reductions in physical and psychological IPV, decreases in parenting practices that could potentially become violent, improvement in overall couples functioning, and increased relationship satisfaction. While all studies reported positive outcomes, their effect sizes ranged from small to large.ConclusionThis study had three main findings: (1) The majority of interventions were for Veterans and/or their partners rather than active service personnel; (2) All interventions reported positive outcomes in the reduction of self-reported IPV, with the majority of these outcomes maintained over time; (3) While we intended to assess military family-level interventions that targeted IPV and CM, we only found three studies that targeted or included CM. Future research should explore how different treatment modalities (e.g., couples, individual, group, in-person, online) could affect long-term IPV treatment outcomes and should focus on how to best incorporate children, including documenting if there are children in the household, into IPV treatments/programs for military families.